Assessing Chicken Rendang in Padang: Quality, Nutrition, and Sensory Analysis - Novia, Deni; Yuherman; Winda Sartika; Rini Rustini (Jurnal Ilmu dan Teknologi Hasil Ternak, 2024)
Chicken rendang is loved by children and adults alike but is still often found in restaurants in Padang City. As a representative of the Minang Region, the city of Padang is very representative of sampling chicken rendang because each rendang has a different process and taste. This research examined the quality, nutritional value, and taste of chicken rendang sold in Padang City. The method used in this research was a survey method with random sampling (purposive sampling), and then laboratory analysis was carried out. Data processing used a 9x2 randomized block design (nine samples and two groups), with samples being places where chicken rendang was taken from 8 restaurants in the city of Padang and one chicken rendang sold commercially (packing) as a control, while quality test without using controls. The parameters observed were quality (FFA, TBA, and cholesterol levels), nutritional value (moisture content, protein content, fat content, ash content), and sensory analysis (color, aroma, texture, and taste of 30 untrained panelists) of chicken rendang. Sample G had the highest nutritional value but was lower than the sensory analysis. On the other hand, the sample I had the highest sensory assessment and high-fat content. Sample D was the best sample regarding quality, nutritional value, and sensory with FFA 0.800%, TBA 0.021 mg malonaldehyde/kg, cholesterol levels 44.35 mg/dl), nutritional value (moisture content 45.03%, protein content 14.48%, fat content 15.44%, ash content 2.80%), and sensory analysis neutral.